An evaluation of dehydrated human amnion/chorion membrane allografts for pressure ulcer treatment: a case series. (1st May 2019) - Berhane, Chi Chi; Brantley, Kimberly; Williams, Sandra; Sutton, Erica; Kappy, Carlyn
Abstract : Objective: Pressure ulcers (PU; also known as pressure injuries) affect about three million adults in the US and cost an estimated $11 billion dollars annually to treat. Prevention is most desirable, however, once a patient develops a PU, the focus shifts to effective treatment and rapid closure to improve health outcomes. We sought to evaluate outcomes in 10 patients with category II and III PUs treated with dehydrated human amnion/chorion membrane (dHACM) allografts. Method: All patients were treated with weekly application of dHACM plus standard wound care (SoC) and followed for eight weeks. Results: Of the PUs, two were category II and eight were category III. The average PU size at dHACM initiation was 3.42±1.76cm 2 . After the first application of dHACM 7/10 (70%) of PUs responded to treatment with a reduction in wound size. Within two weeks of dHACM initiation into the plan of care, 4/10 (40%) of PUs had reduced in size by >50%. By week four, 60% of PUs (6/10) had reduced in size by >50%. Overall, during the eight week evaluation period, 9/10 PUs reduced in size, three of which healed completely. Conclusion: dHACM allografts appear to be a viable treatment option for category II and III PUs.